Effects of exercise on pulse wave velocity in hypertensive and prehypertensive patients: a systematic review and meta-analysis of randomized controlled trials - Xi, Haoyu; Du, Liwen; Li, Gen; Zhang, Shiyan; Li, Xiang; Lv, Yuanyuan; Feng, Lin; Yu, Laikang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aimed to examine the effects of exercise on pulse wave velocity (PWV) in hypertensive and prehypertensive patients.MethodsA comprehensive search was performed in PubMed, Cochrane, Embase, Scopus, and Web of Science, covering data up to August 31, 2023. A meta-analysis was conducted to determine the weighted mean difference (WMD) and 95% confidence interval for the effects of exercise on PWV in hypertensive and prehypertensive patients.ResultsA total of 17 studies met the inclusion criteria. Exercise had a significant effect on improving PWV in hypertensive and prehypertensive patients (WMD, −0.93, P = 0.0001). Subgroup analysis showed that aerobic exercise (WMD, −1.29, P = 0.0004) significantly improved PWV in hypertensive and prehypertensive patients. Moreover, aerobic exercise, specifically moderate-intensity aerobic exercise (WMD, −1.69, P = 0.03), conducted for ≥12 weeks (WMD, −1.54, P = 0.002), ≥3 times per week (WMD, −1.44, P = 0.002), ≤60 min per session (WMD, −1.50, P = 0.02), and ≥180 min per week (WMD, −0.57, P = 0.005), was more effective in improving PWV in hypertensive and prehypertensive patients, especially in middle-aged individuals (WMD, −1.78, P < 0.0001).ConclusionTo improve arterial stiffness, hypertensive and prehypertensive patients, particularly middle-aged individuals, are recommended to participate in a minimum of 12 weeks of moderate-intensity aerobic exercise at least 3 times per week for less than 60 min per session, with a goal of 180 min per week being achieved by increasing the frequency of exercise.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=458981, identifier: CRD42023458981.